2021
DOI: 10.2147/ijgm.s316145
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Significant Pathway Exploration Associated with TOP2A Involved in Papillary Thyroid Cancer

Abstract: Background: Topoisomerase 2-alpha (TOP2A) has been identified as a hub gene that played an important role in the initiation and progression of thyroid carcinoma (THCA). However, the exact function of TOP2A in papillary thyroid cancer (PTC) remained elusive. The current study aimed to evaluate the TOP2A expression, prognosis significance and key signaling pathways involved in PTC. Methods: We firstly evaluated the expression of TOP2A in PTC via UALCAN, cBioportal, HPA and LinkdedOmics databases. Genetic alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…TOP2A has been suggested as a marker of poor prognosis and a potential therapeutic marker in several other cancer types, which make a similar mechanism in PPGL plausible. Similarly to the results presented in this study, Gong et al [24] showed the potential role of TOP2A as a prognostic and therapeutic marker in papillary thyroid cancer as well as Chen et al [25] did in renal cell carcinoma. Like Cluster 1 mutations in PPGL, hypoxia inducible factor (HIF) alterations due to VHL gene mutations are found in renal cell carcinoma, suggesting a potential similar molecular mechanism in PPGL.…”
Section: Discussionsupporting
confidence: 87%
“…TOP2A has been suggested as a marker of poor prognosis and a potential therapeutic marker in several other cancer types, which make a similar mechanism in PPGL plausible. Similarly to the results presented in this study, Gong et al [24] showed the potential role of TOP2A as a prognostic and therapeutic marker in papillary thyroid cancer as well as Chen et al [25] did in renal cell carcinoma. Like Cluster 1 mutations in PPGL, hypoxia inducible factor (HIF) alterations due to VHL gene mutations are found in renal cell carcinoma, suggesting a potential similar molecular mechanism in PPGL.…”
Section: Discussionsupporting
confidence: 87%
“…Mou-chun Gong et al found that TOP2A is a target for two microRNAs including miR-96-5p and miR-635. Based on previous study, miR96-5p signi cantly upregulated in papillary thyroid cancer (PTC) (35). miR-96-5p has a tumor-promoting role in breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Mouchun Gong et al found that TOP2A is a target for two microRNAs including miR-96-5p and miR-635. Based on the previous study, miR96-5p significantly upregulated in papillary thyroid cancer (PTC) [35]. miR-96-5p has a tumor-promoting role in breast cancer.…”
Section: Discussionmentioning
confidence: 96%